Brick's Power Dimension Study Using Fly Ash Additive (Fly Ash) Based on SNI - Syaputri, Wenny Dwi Tiara Ayu; Adha, Idharmahadi; Setyanto, Setyanto (Universitas Lampung, 2015)
The bricks are made from a mixture of soil and water. In this study, the brick-making process willtry to mix the soil with additives (additive) which is fly ash brick (fly ash) to determine how muchbenefit the waste of the additive materials and compare the compressive strength of ordinary brickby brick that has been mixed with additive materials such as fly ash to achieve SNI specificationbricks that’s strong and durable.Soil sample used is a type of clay that comes from the village Yoso Mulyo, Metro. Additivematerials used are fly ash from power plants Tarahan. The variation of dimension used are 4cm x4cm x 4cm, 5cm x 5cm x 5cm, 6cm x 6cm x 6cm, 7cm x 7cm x 7cm. On dimension of 7 cm x 7 cmx7 cm the average compressive strength value is 58,46 cm 2 this is the best compressivestrength.Thus testing the bricks that have been made through the process of mixing, curing andburning, do include specific gravity test compressive strength and water absorption test. Based onthe results of physical testing of the original soil, soil samples Unified system classifies as a fine-grained soil and belongs to the group MLThe results showed that the brick-making post-combustion by using the addition of fly ash as anadditive in a mixture of brick-making material effect on the addition of compressive strengthvalues, so that the power on brick obtained in this study is quite good and meet establishedstandards of the National Standardization Agency for Indonesia (BSNI). The high value of thecompressive strength of the brick using fly ash additive materials due to reduced air volume andpore cavities in the soil particles are filled.Keywords: bricks, fly ash additive, compressive strength